1999
DOI: 10.1074/jbc.274.12.7865
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Transducin α-Subunit α4-Helix/α4-β6 Loop in the Receptor and Effector Interactions

Abstract: The visual GTP-binding protein, transducin, couples light-activated rhodopsin (R*) with the effector enzyme, cGMP phosphodiesterase in vertebrate photoreceptor cells. The region corresponding to the ␣4-helix and ␣4-␤6 loop of the transducin ␣-subunit (G t ␣) has been implicated in interactions with the receptor and the effector. Ala-scanning mutagenesis of the ␣4-␤6 region has been carried out to elucidate residues critical for the functions of transducin. The mutational analysis supports the role of the ␣4-␤6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…Within this stretch of sequence, ET analysis identifies five G ␣ -site 3 residues that are class-specific and surface-exposed, including two residues critical for G t␣ -PDE␥ binding (29), g243 and g244. Residues g306, g307, and g310 are class-specific, and were reported to be involved with PDE␥ binding (30)(31)(32)(33), although recent mutagenesis results have questioned those conclusions (34). Furthermore, residue g209 (205 in G t␣ ) is known to interact with the RGS domain and was shown to have no effect on PDE␥ binding, but mutation to alanine resulted in a substantial decrease in the ability of the mutant G t␣ to bind RGS16 (29).…”
Section: Figmentioning
confidence: 94%
“…Within this stretch of sequence, ET analysis identifies five G ␣ -site 3 residues that are class-specific and surface-exposed, including two residues critical for G t␣ -PDE␥ binding (29), g243 and g244. Residues g306, g307, and g310 are class-specific, and were reported to be involved with PDE␥ binding (30)(31)(32)(33), although recent mutagenesis results have questioned those conclusions (34). Furthermore, residue g209 (205 in G t␣ ) is known to interact with the RGS domain and was shown to have no effect on PDE␥ binding, but mutation to alanine resulted in a substantial decrease in the ability of the mutant G t␣ to bind RGS16 (29).…”
Section: Figmentioning
confidence: 94%
“…Cloning, Expression, and Purification of Chimeric G t ␣/G i ␣ 1 and G i ␣ 1 Subunits-The expression vector pHis6-Gt␣*, which was generously provided by M. Natochin and N. Artemyev, contains a chimeric bovine G t ␣/rat G i ␣ 1 cDNA sequence, preceded by a nucleotide sequence encoding six histidines as an affinity tag (18). The chimeric G␣ protein contains only 16 residues from G i ␣ 1 and was shown to be similar to native G t ␣ in receptor interaction and basal nucleotide exchange.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the known very low expression of the soluble transducin G␣ subunit (G t ␣) in Escherichia coli and Sf9 cells, single amino acid substitutions were introduced into G t ␣ to yield a G t ␣/G i ␣ 1 chimera that contained 16 residues of G i ␣ 1 in a G t ␣ background (18). G i ␣ 1 is not present in photoreceptor cells but belongs to the same G␣ subfamily as G t ␣ and couples to light-activated rhodopsin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, involvement of amino acid sequence 330-350 in the C-terminal region of T ␣ in binding to rhodopsin received further support by alanine scanning, chimeric receptor studies, and peptide-binding studies (9)(10)(11). Additional evidence suggested that the region around residue R310 in T ␣ also is likely to be involved (9,12,13). However, further insights into the contact sites in complex formation between light-activated rhodopsin and T are desirable.…”
mentioning
confidence: 99%